THE EFFECT OF ACTION LEARNING STRATEGIES TOWARD STUDENTS’ SELF-CONFIDENCE IN SPEAKING SKILL - Yusran Maulana Fahmi; Aprianoto; Sugianto (Journal of English Education and Literature, 2026)
Speaking ability is one of the essential skills in language learning; however, many students still face difficulties such as fear, anxiety, and lack of confidence when speaking in public. This study aims to investigate the effect of implementing the Action Learning strategy on students’ self- confidence in speaking skill at SMPN 9 Mataram in the academic year 2024/2025. This research employed a quantitative approach with a quasi- experimental design, specifically the Non-Equivalent Control Group Design. The sample consisted of two classes of eighth-grade students selected through purposive sampling: the experimental class (30 students) was taught using the Action Learning strategy, while the control class (30 students) received conventional instruction. The instruments used were a self-confidence questionnaire and a speaking test, and the data were analyzed using t-tests with the aid of SPSS software. The findings revealed a significant improvement in the experimental class, with the average questionnaire score increasing from 36.1 to 47.9, and the speaking test score rising from 14.2 to 20.1. In contrast, the control class showed only slight and insignificant improvements. The independent-sample t-test confirmed a significant difference between the post-test results of both groups (p < 0.05). Therefore, it can be concluded that the Action Learning strategy has a positive and significant effect on enhancing students’ self-confidence in speaking.